Investigasi RembesanfKebocoran Dinding Suatu KanaVSungai yang Terkontaminasi dengan Metode Resistivitas - Wardoyo, Tri; Mahmudi, Agus (Rekayasa, 2008)
The resistivity method is well used to detecting of existence leakage of river wall. Based on this condition, has been conducted research that correlated with the detecting of leakage of river wall togroundwater. This research was conduct at Gebang River, by using Wenner configuration. Basic Principe of this method, the electrics current (I) was inject into rivers wall through twopotential electrodes. Space of potential electrode used by 10 cm, 20 cm, 30 cm, 40 cm, 50 cm, 60 cm, 70 cm, and 80 cm. Acquisition data presented by electrical potential (V) and electrical current (I). Finall y, found that gained resistivity value that indicated of leakage lowest than before leakage existence.